Cardiovascular and Quality of Life Outcomes of a 3-Month Physical Exercise Program in Two Brazilian Communities - Pereira de Lima, Marcelo; Conopca, Severo; Miyabara, Renata; Romeiro, Geovanna; Campos, Luciana A.; Baltatu, Ovidiu C. (Frontiers in Medicine, 2020)
Background: A decline in physical activity levels in older people is related with worsening of quality of life and a lower cardiorespiratory fitness level, which are associated with cardiovascular disease events and mortality from all causes. Evidence supports the potential impact of community-based physical exercise programs (CEXE) on cardiovascular health and quality of life. The aim of this study was to investigate health-related quality of life (HRQoL) and cardiovascular risk factors of a CEXE in two communities in Brazil. Methods: Adults with an average age of 70.2 ± 5.4 years were recruited to take part in an individually designed group based CEXE program 2-3 times/ week (aerobic exercise, circuit resistance training and stretching exercises for 1 h each time). Once a week were held competitions to develop the socialization and the ability to collaborate among group members. A CEXE group was compared with a sedentary group. Cardiovascular outcomes were blood pressure (BP), triglycerides, body mass index, waist circumference, high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), total cholesterol, and glycaemia. HRQoL was evaluated with the Short Form-36 (SF-36). Results: Of the investigated cardiovascular outcome measures, significantly decreased by the CEXE program were systolic BP (5.7 [95%CI 0.2 to 11.3], p<0.05), and the triglyceride-HDL-C ratio (0.8 [95%CI 0.05 to 1.5], p<0.05), while HDL-C was significantly increased (4.4 [95%CI 0.02 to 8.8], p<0.05). A significant improvement in the SF-36 subscales occurred in CEXE but not in the control group: physical functioning score (increase of 24.2 [95%CI 11.8 to 36.5] vs. -9.2 [95%CI -21.5 to 3.2], p< 0.001), physical role functioning score (increase of 35.4 [95%CI 12.8 to 58.0] vs. 16.7 [95%CI -6.0 to 39.3], p< 0.01) and general health score (increase of 23.7 [95%CI 36.9 to 10.4] vs. 2.4 [95%CI -10.9 to 15.7], p< 0.001). Conclusion: This study shows that a 12-week physical exercise program may significantly improve cardiovascular risk and health-related quality of life measures in older people. An important socio-cultural transferable strategy of our physical exercise program was to develop social activities during and outside the CEXE program.